The Guerrilla Is Like a Poet – Ang Gerilya Ay Tulad ng Makata - Sison, Jose Maria (punctum books, 2021)
This book is titled after the world-renowned poem of Jose Maria Sison, “The Guerrilla Is Like a Poet,” which celebrates with natural imagery and in a lyrical way the Filipino people’s revolutionary struggle for national liberation and democracy against foreign and feudal oppression and exploitation. The book contains poems from Sison’s Prison and Beyond, which won the Southeast Asia WRITE Award, as well as new poems that further develop the theme of struggle for national and social liberation as well as exile. It also carries articles of creative writers on the significance and relevance of his poetry. Sison is a Filipino revolutionary with extensive guerrilla experience and has been a recognized poet since his student days at the University of the Philippines. The publication of this book has been sparked by the effort of the Academy for Cultural Activism of the New World Summit to present the people’s culture in the national democratic struggle in the Philippines.